Crime and punishment in Russia: a comparative history from Peter the Great to Vladimir Putin - Daly, Jonathan W. (The Bloomsbury history of modern Russia series, 2018)
Eighteenth-century Russia -- Nineteenth-century Russia before the emancipation -- From the great reforms to revolution -- The era of Lenin -- The era of Stalin -- The USSR under "mature socialism" -- Criminal justice since the collapse of communism -- Conclusion -- Glossary -- Works cited